2021
DOI: 10.3390/nano11113059
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Mediated Co-Existence of Single-Walled Carbon Nanotube Networks and Cellulose Nanocrystal Mesophases

Abstract: Hybrids comprising cellulose nanocrystals (CNCs) and percolated networks of single-walled carbon nanotubes (SWNTs) may serve for the casting of hybrid materials with improved optical, mechanical, electrical, and thermal properties. However, CNC-dispersed SWNTs are depleted from the chiral nematic (N*) phase and enrich the isotropic phase. Herein, we report that SWNTs dispersed by non-ionic surfactant or triblock copolymers are incorporated within the surfactant-mediated CNC mesophases. Small-angle X-ray measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Experimental investigations have addressed the adsorption of surfactants and lipid molecules dissolved in aqueous solutions on CNTs [ 10 , 11 , 12 , 13 , 14 ]. Transmission electron microscopy experiments have shown that single-tailed phospholipids form supramolecular complexes on the surface of CNTs [ 10 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations have addressed the adsorption of surfactants and lipid molecules dissolved in aqueous solutions on CNTs [ 10 , 11 , 12 , 13 , 14 ]. Transmission electron microscopy experiments have shown that single-tailed phospholipids form supramolecular complexes on the surface of CNTs [ 10 , 15 ].…”
Section: Introductionmentioning
confidence: 99%